ANALISIS KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN IPAS PADA KURIKULUM MERDEKA DI SDN KARANG TENGAH 8 KOTA TANGERANG - Marshanda Istikharah; Ferry Perdiansyah; Najib Hasan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Curriculum changes always bring new dynamics into the classroom, especially when Science and Social Studies are integrated into IPAS within the Merdeka Curriculum. The focus on contextual learning, project-based activities, real-life experiences, and strengthening the values of the Pancasila Student Profile does not always run smoothly in practice. This study aims to capture the learning difficulties faced by grade V students at SDN Karang Tengah 8, Tangerang City, particularly in the topic of light. Using a qualitative descriptive approach, data were collected through observation, interviews, tests, and documentation involving 29 students as research subjects. The findings reveal various challenges, including weak mastery of the material, concentration problems, low motivation, and limited access to textbooks. Environmental factors and basic literacy skills such as reading and writing also played a significant role in shaping these difficulties. A total of 11 students did not reach the minimum competency score (KKM) and displayed clear indicators of learning difficulties, such as low achievement, slow task completion, and emotional or unusual behaviors during lessons. Nevertheless, several solutions can be applied, including more engaging and active learning models through differentiation, adequate availability of learning resources, and strong support from teachers, schools, and parents. With consistent collaboration, the challenges in IPAS learning can be transformed into opportunities to strengthen the spirit of independent learning.